The Effects of Black Garlic on Ovarian Malondialdehyde, Oviduct Muscle, and Endometrial Arterioles in Smoke-Exposed Rats - Anandasari, Noni Fidya Ayu; Kridayanti, Novalia; Kaspirayanthi, Ni Ketut Devy; Nurseta, Tatit; Raras, Tri Yudani Mardining; Khotimah, Husnul; Reksohusodo, Subandi; Anita, Kenty Wantri; Yudhanto, Hendy Setyo (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
The effect of cigarette smoke exposure on reproductive health has been widely studied, showing various physiological disorders induced by free radicals and oxidative stress. This study aimed to assess the protective effect of ethanol extract of black garlic (Allium sativum) on some reproductive parameters of female rats Rattus norvegicus exposed to subacute cigarette smoke. A proper experimental method with a post-test-only control group design was used, involving 25 rats divided into five groups with three different doses of the extract. The rats were exposed to cigarette smoke and then treated for 28 days. Results showed a significant decrease in ovarian Malondialdehyde levels and increased fallopian tube smooth muscle thickness in the extract-treated group. In addition, black garlic extract successfully increased the number of endometrial arterioles in the group exposed to cigarette smoke and extract, in contrast to the group exposed to cigarette smoke only. This study concludes that black garlic extract has the potential to be a protective agent against oxidative damage in the reproductive system of rats exposed to cigarette smoke, with effectiveness that depends on the dose of extract given. Further studies should investigate the long-term effects and optimal dosing of black garlic extract in humans. Additionally, exploring the molecular mechanisms behind its protective properties could enhance its application in reproductive health management.